2009
DOI: 10.1097/rli.0b013e3181911eab
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Gadobenate Dimeglumine for Imaging Of Chronic Myocardial Infarction in Comparison With Standard Dose Gadopentetate Dimeglumine

Abstract: Low dose Gd-BOPTA resulted in significantly higher CNRinf-myo compared with standard dose Gd-DTPA in imaging of myocardial infarction with IR SSFP and IR GRE sequences. Demarcation of infarcted myocardium from the left ventricular cavity assessed by CNR showed no significant difference after application of either contrast media in both imaging techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 45 publications
1
18
0
1
Order By: Relevance
“…As previously reported by other authors [15][16][17][18]20], a gadobenate dimeglumine dose of 0.1 mmol/kg BW generally provides an excellent image quality for determinations of IM size and volume.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…As previously reported by other authors [15][16][17][18]20], a gadobenate dimeglumine dose of 0.1 mmol/kg BW generally provides an excellent image quality for determinations of IM size and volume.…”
Section: Discussionmentioning
confidence: 62%
“…Comparative CMR studies, both inter-individually [15,16] and intra-individually [17,18], have similarly shown that a dose of 0.1 mmol/kg BW Gd-BOPTA is equivalent to a double 0.2 mmol/kg BW dose of Gd-DTPA in terms of both scar depiction and quantification of necrotic tissue.…”
Section: Introductionmentioning
confidence: 92%
“…For each variable, the box represents mean±standard deviation, whereas the vertical segment defines the observed range. Signal Intensity Contrast-to-noise ratio possible alternative approach is the intraindividual design, administering both contrast agents to each patient, as was done in two recent studies [8,11]. At any rate, our study should be regarded as a preliminary retrospective evaluation of the differences between Gd-BOPTA and a standard relaxivity contrast agent (Gd-DOTA) at the single dose of 0.1 mmol/kg, which provides a rationale for planning a randomized or an intraindividual study.…”
Section: Discussionementioning
confidence: 99%
“…However, this approach has the double drawback of an unvaoidable lack of (histopathological) reference standard and the possible variability of the incidence of subendocardial infarctions in the two study arms. A bassa dose di Gd-BOPTA è migliore [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation